Some aspects of creating individual splint systems - Носова, Я. В.; Худаєва, С. А.; Nosova, Ya.; Khudaieva, S. A.; Ibrahim Younouss Abdelhamid; Chygrinova, E. A.; Perepelitsa, A. (RS Global, 2020)
Some aspects of creating individual splint systems are described.
Keywords: nasal breathing; wall nasal splint system; three-dimensional model; prototyping